Desenvolvimento de gel mucoadesivo para o tratamento de candidíase oral a partir do extrato de Schinopsis brasiliensis Engler - Araújo, René Monteiro (2017)
Of the several species that make up the Candida genus, some have been shown to be associated with cases of human infection, with Candida albicans being the main pathogen, despite studies confirming cases of infection with other species of the genus. There are several drugs available for the treatment of oral candidiasis, and nystatin is the drug of first choice. However, in addition to its known side effects, nystatin does not present considerable residual action, which impairs treatment efficiency. Given this, this work aims to develop a mucoadhesive gel for the treatment of oral candidiasis, constituted by extract of S. brasiliensis, encapsulated in maltodextrin nanoparticles. After obtaining the extract by maceration followed by rotary evaporation, the assay was performed to verify the antifungal activity of the same, by the microdilution method in broth, using 96-well microplates. This was done with the assay to elucidate the possible mechanism of action of the extract on the wall and fungal cell membrane, by the microdilution method. Then, the phytochemical prospection was carried out, searching for the main phytocomponents of the plant, by spectrophotometry, in order to associate their presence with the antifungal action of the plant. Subsequently, the microparticles of maltodextrin were developed by Spray Drier, encapsulating the extract, varying the flow rate of the pump. Subsequently, the microparticle that had the best fungal activity was selected to follow the steps of thermal compatibility, formulation and evaluation of its effectiveness.